The Influence of Gender and Personality Traits on Customer’s Assessment of Islamic Banking Service Quality - Sri Rahayu, Yayuk; Aslamatis S, Nihayatu (International Journal of Engineering and Technology, 2019)
Background: The competition in the banking business increased concurrently with the growth of both conventional and Islamic banking and to win the competition, the bank must provide a qualified service. Personality of employees in providing services affects the quality of service perceived by the customer and customerâ€™s assessment on service quality is also determined by gender. Objectives: This study aims to investigate the influence of gender and personality traitsÂ simultaneously and partially on service quality of Islamic banking. It is also to determine which variables are the dominant influences on service quality of Islamic banking. Results: The1result showed that gender and personality influenced simultaneously on a customerâ€™s assessment of the Islamic banking service quality. Variables that influenced partially on Islamic banking service quality were gender, extraversion and agreeableness while openness, conscientiousness, and neuroticism did not influence partially on service quality of Islamic banking. In addition, gender had dominant influence on service quality of1 Islamic banking. Conclusion: Islamic banking should pay attention1 to the culture of local community associated with gender. So, the sustainability of relationships between1 Islamic Banking with local community will be maintainedÂ